ADHM polytopes - James P. Allen; Paul Sutcliffe (Journal of High Energy Physics, 2013)
Despite advances in combined photothermal (PTT) and photodynamic (PDT) therapy for melanoma, therapeutic efficacy remains limited by tumor hypoxia, intracellular glutathione (GSH), insufficient tumor targeting, and photobleaching of photosensitizers. Herein, tumor-targeting and GSH self-depleting hyaluronic acid (HA)/tannic acid (TA)-engineered Prussian blue (PB) oxygen nanogenerators (ONs) loaded with IR780 (IHTPB ONs) are developed to enhance synergistic PTT/PDT. The IHTPB ONs exhibit uniform morphology, excellent colloidal stability, acidity/GSH-responsive IR780 release, high photothermal conversion efficiency (60%), and outstanding photothermal stability. Importantly, PB-mediated GSH oxidation and TA-mediated GSH conjugation enable dual-mode GSH depletion, while PB catalyzes oxygen generation to alleviate tumor hypoxia and promote IR780-mediated singlet oxygen production. Following CD44-mediated cellular uptake, IHTPB ONs effectively deplete intracellular GSH and, under near-infrared irradiation, induce robust reactive oxygen species generation and hyperthermia, leading to mitochondrial dysfunction, lipid peroxidation, apoptosis, and ferroptosis. In vivo, IHTPB ONs exhibit superior tumor accumulation and significantly enhanced antitumor efficacy compared with free IR780 and non-targeted nanoparticles, resulting in prolonged survival of melanoma-bearing mice. This work provides an effective nanoplatform integrating tumor targeting, oxygen self-supply, and dual-mode GSH depletion to potentiate synergistic PTT/PDT for melanoma therapy.